Cathepsin K activity controls cachexia‐induced muscle atrophy via the modulation of IRS1 ubiquitination. Issue 2 (30th January 2022) - Meng, Xiangkun; Huang, Zhe; Inoue, Aiko; Wang, Hailong; Wan, Ying; Yue, Xueling; Xu, Shengnan; Jin, Xueying; Shi, Guo‐Ping; Kuzuya, Masafumi; Cheng, Xian Wu
Abstract: Background: Cachexia is a complicated metabolic disorder that is characterize by progressive atrophy of skeletal muscle. Cathepsin K (CTSK) is a widely expressed cysteine protease that has garnered attention because of its enzymatic and non‐enzymatic functions in signalling in various pathological conditions. Here, we examined whether CTSK participates in cancer‐induced skeletal muscle loss and dysfunction, focusing on protein metabolic imbalance. Methods: Male 9‐week‐old wild‐type (CTSK +/+, n  = 10) and CTSK‐knockout (CTSK −/−, n  = 10) mice were injected subcutaneously with Lewis lung carcinoma cells (LLC; 5 × 10 5 ) or saline, respectively. The mice were then subjected to muscle mass and muscle function measurements. HE staining, immunostaining, quantitative polymerase chain reaction, enzyme‐linked immunosorbent assay, and western blotting were used to explore the CTSK expression and IRS1/Akt pathway in the gastrocnemius muscle at various time points. In vitro measurements included CTSK expression, IRS1/Akt pathway‐related target molecule expressions, and the diameter of C2C12 myotubes with or without LLC‐conditioned medium (LCM). An IRS1 ubiquitin assay, and truncation, co‐immunoprecipitation, and co‐localization experiments were also performed. Results: CTSK +/+ cachectic animals exhibited loss of skeletal muscle mass (muscle weight loss of 15%, n  = 10, P  < 0.01), muscle dysfunction (grip strength loss > 15%, n  = 10, P  < 0.01), and fibre area (average area reduction > 30%, n  = 5, P  < 0.01). Compared with that of non‐cachectic CTSK +/+ mice, the skeletal muscle of cachectic CTSK +/+ mice exhibited greater degradation of insulin receptor substrate 1 (IRS1, P  < 0.01). In this setting, cachectic muscles exhibited decreases in the phosphorylation levels of protein kinase B (Akt 308, P  < 0.01; Akt 473, P  < 0.05) and anabolic‐related proteins (the mammalian target of rapamycin, P  < 0.01) and increased levels of catabolism‐related proteins (muscle RING‐finger protein‐1, P  < 0.01; MAFbx1, P  < 0.01) in CTSK +/+ mice ( n  = 3). Although there was no difference in LLC tumour growth ( n  = 10, P  = 0.44), CTSK deletion mitigated the IRS1 degradation, loss of the skeletal muscle mass ( n  = 10, P  < 0.01), and dysfunction ( n  = 10, P  < 0.01). In vitro, CTSK silencing prevented the IRS1 ubiquitination and loss of the myotube myosin heavy chain content ( P  < 0.01) induced by LCM, and these changes were accelerated by CTSK overexpression even without LCM. Immunoprecipitation showed that CTSK selectively acted on IRS1 in the region of amino acids 268 to 574. The results of co‐transfection of IRS1‐N‐FLAG or IRS1‐C‐FLAG with CTSK suggested that CTSK selectively cleaves IRS1 and causes ubiquitination‐related degradation of IRS1. Conclusions: These results demonstrate that CTSK plays a novel role in IRS1 ubiquitination in LLC‐induced muscle wasting, and suggest that CTSK could be an effective therapeutic target for cancer‐related cachexia.